The Power of Digital Communication in Scaling Remote Engineering Teams: An Interview-Based Study on Cultural Diversity and Challenges in Telecommuting - Aquino, Trishia Joyce D.; Cordero, Angela Faith F.; Culla, Anne Katherine C.; Manliclic, Sid Nicolas J.; Pineda, Jr. , Florentino G.; Rafael, Charlie Jay C. (Future Science / FSH-PH Publications, 2024)
ABSTRACT In this day and age, the world has slowly been shifting to the widespread use of technology in almost all aspects, including employment. This is proven by the continuous growth in the number of remote jobs globally, which allows people to work from home through the use of technology anytime and anywhere. Naturally, challenges and dilemmas, especially when it comes to communication, arise in the workplace. However, the challenges experienced in the face-to-face setup may differ from what is experienced in a remote or online setup. That being said, this research aims to discover the organizational culture being practiced in a remote work setup, specifically its organizational culture, communication flow, and practices, as well as the communication model being observed in the workplace through the conduction of an interview between two engineers. The findings reveal that the organization has both linguistic diversity and cultural pluralism. Moreover, their primary communication channels are digital tools, which is an indication that the Interactive model of communication is observed in their company. In addition, employees, irrespective of their positions, are also given the chance to participate and talk during meetings, which signifies that the company's communication flows are both vertical and horizontal. Lastly, technological barriers like internet connectivity impact project development, which may lead to miscommunications in the workplace. Overall, the research sheds light on communication challenges and practices in remote work environments while also highlighting the healthy work atmosphere the selected organization has cultivated.